Fireproof flame-retardant polymer composite material

The fire-retardant polymer composite material addresses compatibility and efficiency issues by integrating synergistic flame retardants with polyamide and polyurethane, enhancing thermal stability and mechanical strength through steric hindered groups and heterocyclic structures, forming a protective carbon layer.

CN119192827AInactive Publication Date: 2024-12-27CHANGSHENG XINLIAN ECOLOGICAL IND DEVELOPMENT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411282545.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing polymer materials suffer from poor compatibility between flame retardants and substrates, low flame retardant efficiency, and a negative impact on mechanical properties under high temperature conditions.

Method used

A fire-retardant polymer composite material comprising polyamide, polyurethane, a synergistic flame retardant, lubricant, and antioxidant, prepared by a specific synthesis process involving binaphthol phosphate, 9,9'-(6-chloro-1,3,5-triazine-2,4-diyl)bis(9H-carbazole), and heterocyclic diamine monomers, which introduce steric hindered groups and heterocyclic structures for enhanced thermal stability and mechanical strength.

Benefits of technology

The composite material exhibits improved thermal stability, flame retardant properties, and mechanical strength, forming a stable carbon layer that reduces thermal decomposition and combustion, while maintaining mechanical integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192827A_ABST
    Figure CN119192827A_ABST
Patent Text Reader

Abstract

Belonging to the technical field of flame retardant materials, the invention discloses a fireproof flame retardant polymer composite material, which comprises the following components by weight: 20-60 parts of polyamide, 10-50 parts of polyurethane, 2-10 parts of a synergistic flame retardant, 1-5 parts of a lubricant, 1-2 parts of an antioxidant, and 1-5 parts of an anti-aging agent. The binaphthol phosphate provided by the invention contains a phosphorus-containing seven-membered macroring, and a triazinyl group and a carbazolyl group which are contained on 9, 9 '-(6-chloro-1, 3, 5-triazine-2, 4-diyl) bis (9H-carbazole), and a plurality of large steric hindrance groups with non-coplanar structures are introduced into a synergistic flame retardant through the reaction of the triazinyl group and the carbazolyl group; the thermal stability and the flame retardant property of the composite material are improved through heterocyclic groups on the heterocyclic diamine monomer, and the synergistic flame retardant effect of nitrogen and phosphorus elements is fully exerted; the composite material has good char forming capability and molten drop resistance; the synergistic flame retardant and the matrix have excellent compatibility, the problem that the mechanical property is reduced due to addition of a traditional flame retardant is effectively prevented, the structural rigidity of the material is improved through the synergistic flame retardant, and the overall mechanical strength of the composite material is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of flame retardant materials, and in particular relates to a fireproof and flame retardant polymer composite material. Background Art

[0002] With the advancement of science and technology, polymer materials have become an indispensable component of many industrial fields. Natural and synthetic polymers play a variety of roles in modern industries due to their superior lightness and chemical resistance. These materials show their unique value in applications such as automobiles, packaging, textiles, construction and biomedicine. However, synthetic polymers are prone to decomposition under extreme temperature conditions, which directly affects the reliability of the materials and the feasibility of long-term applications. With the increasing dependence on polymer materials, the risk of fire caused by polymer materials is also coming. The damage to life and economy caused by these risks cannot be ignored. Therefore, enhancing the stability of polymer materials under high temperature conditions and improving their fire retardant properties are of great significance to meet the growing industrial needs and ensure social security.

[0003] Adding flame retardants to polymer materials is an important way to improve high temperature resistance and fire retardant properties. Polymer flame retardants are usually divided into the following three types:

[0004] (1) Additive polymer flame retardant materials, through high-speed mechanical mixing, the flame retardant is evenly dispersed in the polymer material to obtain flame retardant properties;

[0005] (2) Reactive polymer flame retardants, which use flame retardants as reactant monomers and are bonded to the polymer main chain or side chain through chemical reactions to obtain flame retardant properties;

[0006] (3) Through chemical reactions, monomers containing flame retardant elements are used as raw materials to synthesize polymer flame retardant materials, making them flame retardant themselves.

[0007] However, these flame retardants still have some defects when used, such as poor compatibility between the flame retardants and the substrate, low flame retardant efficiency, and affecting the mechanical properties of the materials. Summary of the invention

[0008] In view of the above situation, in order to overcome the defects of the prior art, the present invention improves the flame retardant and provides a polymer composite material that can give full play to the synergistic flame retardant effect of nitrogen and phosphorus elements and has good mechanical properties while maintaining flame retardant properties.

[0009] In order to achieve the above object, the following technical scheme is adopted: The present invention provides a fire-retardant polymer composite material, comprising the following components in parts by weight:

[0010] 20-60 parts of polyamide, 10-50 parts of polyurethane, 2-10 parts of synergistic flame retardant, 1-5 parts of lubricant, 1-2 parts of antioxidant, and 1-5 parts of antioxidant.

[0011] Furthermore, the synergistic flame retardant is prepared by the following steps:

[0012] (1) Under nitrogen protection, dissolving binaphthol phosphate and 9,9'-(6-chloro-1,3,5-triazine-2,4-diyl)bis(9H-carbazole) in N,N-dimethylformamide, heating to 110°C, stirring continuously for 5 hours, cooling to room temperature, filtering to obtain a granular precipitate, filtering, washing the precipitate three times with petroleum ether, and drying at 80°C for 12 hours to obtain an intermediate;

[0013] (2) Under nitrogen protection, the intermediate, heterocyclic diamine monomer, N-methyl-2-pyrrolidone, anhydrous potassium carbonate and xylene are mixed uniformly, heated to 150° C., and reacted for 6 hours. After the reaction is completed, the mixture is heated to 180° C. until the reaction system becomes viscous. An excess of 2 mol / L hydrochloric acid is added to the reaction system, and the mixture is stirred until a flocculent precipitate is produced. The precipitate is filtered, washed three times with deionized water, and dried at 90° C. for 12 hours to obtain the synergistic flame retardant.

[0014] Furthermore, in the step (1), the feed mass ratio of binaphthol phosphate, 9,9'-(6-chloro-1,3,5-triazine-2,4-diyl)bis(9H-carbazole) and N,N-dimethylformamide is 20-45:10-30:120-200.

[0015] Furthermore, in the step (2), the mass ratio of the intermediate, the heterocyclic diamine monomer, N-methyl-2-pyrrolidone, anhydrous potassium carbonate and xylene is 12-42:18-38:80-150:5-12:30-50.

[0016] Furthermore, the heterocyclic diamine monomer is one of 2-(4-aminophenyl)-5-aminobenzimidazole, 2-(4-aminophenyl)-5-aminobenzoxazole, and 2,5-bis(4-aminophenyl)oxadiazole.

[0017] Furthermore, the weight average molecular weight of the polyimide is 20,000-40,000, and the weight average molecular weight of the polyurethane is 20,000-30,000.

[0018] Furthermore, the lubricant is a combination of one or more of sodium bentonite, calcium bentonite, graphite, zinc naphthenate, and molybdenum disulfide.

[0019] Furthermore, the antioxidant is a combination of one or more of ammonium polyphosphate, melamine, 2-mercaptobenzimidazole, N-phenyl-α-naphthylamine, and N-(1,3-dimethylbutyl)-N'-phenyl-1,4-phenylenediamine.

[0020] Furthermore, the antioxidant is a combination of one or more of tris(2,4-di-tert-butyl)phenyl phosphite, tris(2,4-di-tert-butylphenyl) phosphite, pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)phenylpropionate, and bis-(2,4-di-tert-butylphenyl)-pentaerythritol diphosphite.

[0021] Furthermore, the preparation is carried out through the following steps: polyamide and polyurethane are mixed evenly, added into a twin-screw extruder, a synergistic flame retardant, a lubricant, an antioxidant and an anti-aging agent are added into the middle section of the twin-screw extruder, melt-extruded through the twin-screw extruder, and dried to obtain the polymer composite material.

[0022] Furthermore, the temperature of the twin-screw extruder is 220-270°C.

[0023] The beneficial effects of the present invention are:

[0024] (1) The present invention contains a phosphorus-containing seven-membered macrocyclic ring on the binaphthol phosphate and a triazine group and a carbazole group on 9,9'-(6-chloro-1,3,5-triazine-2,4-diyl)bis(9H-carbazole), and the two react to introduce multiple large steric hindered groups with non-coplanar structures into the synergistic flame retardant, and the heterocyclic groups on the heterocyclic diamine monomer effectively improve the thermal stability and flame retardant properties of the composite material, and the synergistic flame retardant effect of nitrogen and phosphorus elements can be fully exerted through a variety of nitrogen and phosphorus groups and nitrogen and phosphorus heterocyclic groups;

[0025] (2) The composite material of the present invention has good carbonization ability and anti-melting droplet performance, because the synergistic flame retardant contains a large number of heat-resistant aromatic groups and heterocyclic groups, which produce phosphoric acid derivatives such as phosphoric acid and polyphosphoric acid, and promote the formation of a stable carbon layer on the surface of the polymer matrix. The carbon layer has an isolating effect on the flame, which can effectively reduce the temperature of the material surface and slow down the thermal decomposition and combustion rate inside the material;

[0026] (3) The synergistic flame retardant of the present invention exhibits excellent compatibility with polyamide and polyurethane matrices, which effectively prevents the problem of decreased mechanical properties caused by the addition of traditional flame retardants. The phosphorus-containing seven-membered macrocyclic ring and large steric hindrance group in the synergistic flame retardant not only improve the structural rigidity of the material, but also enhance the overall mechanical strength of the composite material, ensuring that the material has good mechanical properties while maintaining flame retardant properties, meeting the needs of high-intensity application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1The flame retardant performance test results of various embodiments and comparative examples of a fire-retardant polymer composite material of the present invention;

[0028] Figure 2 The thermal weight loss test results of various embodiments and comparative examples of a fire-retardant polymer composite material of the present invention;

[0029] Figure 3 The tensile strength and elongation at break test results of various embodiments and comparative examples of a fire-retardant polymer composite material of the present invention are shown in FIG.

[0030] Figure 4 The SEM images of the carbon residue after the thermal gravimetric test of Example 3 and Comparative Example 1 of the fire-retardant polymer composite material of the present invention are shown.

[0031] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0033] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0034] The experimental methods in the following examples are conventional methods unless otherwise specified, and the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified. DOPO flame retardant was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0035] Example 1

[0036] A fire-retardant polymer composite material

[0037] The composite material comprises the following components in parts by weight:

[0038] 20 parts of polyamide, 10 parts of polyurethane, 2 parts of synergistic flame retardant, 1 part of lubricant, 1 part of antioxidant, and 1 part of antioxidant.

[0039] The synergistic flame retardant is prepared by the following steps:

[0040] (1) Under nitrogen protection, dissolving binaphthol phosphate and 9,9'-(6-chloro-1,3,5-triazine-2,4-diyl)bis(9H-carbazole) in N,N-dimethylformamide, heating to 110°C, stirring continuously for 5 hours, cooling to room temperature, filtering to obtain a granular precipitate, filtering, washing the precipitate three times with petroleum ether, and drying at 80°C for 12 hours to obtain an intermediate;

[0041] (2) Under nitrogen protection, the intermediate, heterocyclic diamine monomer, N-methyl-2-pyrrolidone, anhydrous potassium carbonate and xylene are mixed uniformly, heated to 150° C., and reacted for 6 hours. After the reaction is completed, the mixture is heated to 180° C. until the reaction system becomes viscous. An excess of 2 mol / L hydrochloric acid is added to the reaction system, and the mixture is stirred until a flocculent precipitate is produced. The precipitate is filtered, washed three times with deionized water, and dried at 90° C. for 12 hours to obtain the synergistic flame retardant.

[0042] In the step (1), the feed mass ratio of binaphthol phosphate, 9,9'-(6-chloro-1,3,5-triazine-2,4-diyl)bis(9H-carbazole) and N,N-dimethylformamide is 20:10:120.

[0043] In the step (2), the feed mass ratio of the intermediate, the heterocyclic diamine monomer, N-methyl-2-pyrrolidone, anhydrous potassium carbonate and xylene is 12:18:80:5:30.

[0044] The heterocyclic diamine monomer is 2-(4-aminophenyl)-5-aminobenzimidazole.

[0045] The weight average molecular weight of the polyimide is 20,000-40,000, and the weight average molecular weight of the polyurethane is 20,000-30,000.

[0046] The lubricant is obtained by mixing sodium-based bentonite, calcium-based bentonite and graphite in a mass ratio of 1:1:1.

[0047] The antioxidant is prepared by mixing ammonium polyphosphate, melamine, N-phenyl-α-naphthylamine and N-(1,3-dimethylbutyl)-N'-phenyl-1,4-phenylenediamine in a mass ratio of 2.5:1.5:2:1.

[0048] The antioxidant is obtained by mixing tri(2,4-di-tert-butyl)phenyl phosphite and tri(2,4-di-tert-butylphenyl) phosphite in a mass ratio of 2:1.

[0049] The preparation is carried out by the following steps: polyamide and polyurethane are mixed evenly, added into a twin-screw extruder, a synergistic flame retardant, a lubricant, an antioxidant and an anti-aging agent are added into the middle section of the twin-screw extruder, melt-extruded at 220° C. through a twin-screw extruder, and dried to obtain the polymer composite material.

[0050] Example 2

[0051] A fire-retardant polymer composite material

[0052] The composite material comprises the following components in parts by weight:

[0053] 60 parts of polyamide, 50 parts of polyurethane, 10 parts of synergistic flame retardant, 5 parts of lubricant, 2 parts of antioxidant, and 5 parts of antioxidant.

[0054] The preparation process of the synergistic flame retardant is the same as that of Example 1.

[0055] In the step (1), the feed mass ratio of binaphthol phosphate, 9,9'-(6-chloro-1,3,5-triazine-2,4-diyl)bis(9H-carbazole) and N,N-dimethylformamide is 45:30:200.

[0056] In the step (2), the feed mass ratio of the intermediate, the heterocyclic diamine monomer, N-methyl-2-pyrrolidone, anhydrous potassium carbonate and xylene is 42:38:150:12:50.

[0057] The heterocyclic diamine monomer is 2-(4-aminophenyl)-5-aminobenzoxazole.

[0058] The weight average molecular weight of the polyimide is 20,000-40,000, and the weight average molecular weight of the polyurethane is 20,000-30,000.

[0059] The lubricant is prepared by mixing calcium-based bentonite, graphite and zinc naphthenate in a mass ratio of 2:1:3.

[0060] The antioxidant is prepared by mixing ammonium polyphosphate, 2-mercaptobenzimidazole, N-phenyl-α-naphthylamine and N-(1,3-dimethylbutyl)-N'-phenyl-1,4-phenylenediamine in a mass ratio of 2:1:2:2.

[0061] The antioxidant is pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)phenylpropionate.

[0062] The preparation is carried out by the following steps: polyamide and polyurethane are mixed evenly, added into a twin-screw extruder, a synergistic flame retardant, a lubricant, an antioxidant and an anti-aging agent are added into the middle section of the twin-screw extruder, melt-extruded at 270° C. through a twin-screw extruder, and dried to obtain the polymer composite material.

[0063] Example 3

[0064] A fire-retardant polymer composite material

[0065] The composite material comprises the following components in parts by weight:

[0066] 40 parts of polyamide, 30 parts of polyurethane, 8 parts of synergistic flame retardant, 2 parts of lubricant, 1.5 parts of antioxidant, and 3.5 parts of antioxidant.

[0067] The preparation process of the synergistic flame retardant is the same as that of Example 1.

[0068] In the step (1), the feed mass ratio of binaphthol phosphate, 9,9'-(6-chloro-1,3,5-triazine-2,4-diyl)bis(9H-carbazole) and N,N-dimethylformamide is 32:25:135.

[0069] In the step (2), the feed mass ratio of the intermediate, the heterocyclic diamine monomer, N-methyl-2-pyrrolidone, anhydrous potassium carbonate and xylene is 25:25:130:7.5:42.

[0070] The heterocyclic diamine monomer is 2,5-di(4-aminophenyl)oxadiazole.

[0071] The weight average molecular weight of the polyimide is 20,000-40,000, and the weight average molecular weight of the polyurethane is 20,000-30,000.

[0072] The lubricant is obtained by mixing sodium bentonite, calcium bentonite, zinc cyclohexaneate and molybdenum disulfide in a mass ratio of 1:2:2:4.

[0073] The antioxidant is obtained by mixing ammonium polyphosphate, melamine and N-(1,3-dimethylbutyl)-N'-phenyl-1,4-phenylenediamine in a mass ratio of 1:2:2.

[0074] The antioxidant is obtained by mixing pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)phenylpropionate and bis-(2,4-di-tert-butylphenyl)-pentaerythritol diphosphite in a mass ratio of 1:3.

[0075] The preparation is carried out by the following steps: polyamide and polyurethane are mixed evenly, added into a twin-screw extruder, a synergistic flame retardant, a lubricant, an antioxidant and an anti-aging agent are added into the middle section of the twin-screw extruder, melt-extruded at 250° C. through a twin-screw extruder, and dried to obtain the polymer composite material.

[0076] Comparative Example 1

[0077] The difference between this comparative example and Example 3 is that an equal amount of binaphthol phosphate is used to replace the synergistic flame retardant, and the remaining components, component contents, and preparation process are the same as those of Example 3.

[0078] Comparative Example 2

[0079] The difference between this comparative example and Example 3 is that an equal amount of dinaphthol phosphate is used instead of the intermediate to prepare the synergistic flame retardant, and the remaining components, component contents, and preparation process are the same as those in Example 3.

[0080] Comparative Example 3

[0081] The difference between this comparative example and Example 3 is that an equal amount of commercially available DOPO flame retardant is used to replace the synergistic flame retardant, and the remaining components, component contents, and preparation process are the same as those in Example 3.

[0082] Results Analysis

[0083] The flame retardant properties of each embodiment and comparative example were tested by JF-5 instrument according to the standard of ASTM D2863. The results are as follows: Figure 1 shown.

[0084] The thermogravimetric test of each embodiment and comparative example was performed by STA499F3 synchronous thermal analyzer, and the results are as follows: Figure 2 shown.

[0085] The tensile strength and elongation at break of each embodiment and comparative example were tested by INSTRON5565 universal material testing machine according to the test standard of ISO 527-2. The results are as follows: Figure 3 As shown, the test condition is a tensile rate of 10 mm / min.

[0086] From the above test results, it can be seen that Examples 1-3 have a higher limiting oxygen index, a higher thermal decomposition temperature, and the tensile strength and elongation at break are all higher than those of the comparative example, which proves that the composite material prepared by the present invention has higher thermal stability and fire retardant properties, and the synergistic flame retardant effect of nitrogen and phosphorus elements is fully exerted through the synergistic effect of binaphthol phosphate, 9,9'-(6-chloro-1,3,5-triazine-2,4-diyl)bis(9H-carbazole) and heterocyclic diamine monomers.

[0087] Figure 4 The SEM images of the carbon residue after the thermal gravimetric test, wherein (a)-(d) represent Example 3, Comparative Example 1, Comparative Example 2 and Comparative Example 3, respectively.

[0088] from Figure 4It can be seen from the analysis results that after the thermogravimetric analysis, the composite material of Example 3 has a smooth and complete appearance, while obvious pores and cracks are observed in the composite materials of Comparative Examples 1-3, which indicates that the composite material of Example 3 can form a solid carbonaceous protective layer under high temperature environment, which has a flame blocking effect, helps to reduce heat accumulation on the surface of the material, and inhibits thermal decomposition and combustion process inside the material.

[0089] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

[0090] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A fire-retardant polymer composite material, characterized in that: The composition comprises the following components in parts by weight: Polyamide 20-60 parts, polyurethane 10-50 parts, synergistic flame retardant 2-10 parts, lubricant 1-5 parts, antioxidant 1-2 parts, antioxidant 1-5 parts; The synergistic flame retardant is prepared by the following steps: (1) Under nitrogen protection, dissolving binaphthol phosphate and 9,9'-(6-chloro-1,3,5-triazine-2,4-diyl)bis(9H-carbazole) in N,N-dimethylformamide, heating to 110°C, stirring continuously for 5 hours, cooling to room temperature, filtering to obtain a granular precipitate, filtering, washing the precipitate three times with petroleum ether, and drying at 80°C for 12 hours to obtain an intermediate; (2) Under nitrogen protection, the intermediate, heterocyclic diamine monomer, N-methyl-2-pyrrolidone, anhydrous potassium carbonate and xylene are mixed uniformly, heated to 150° C., and reacted for 6 hours. After the reaction is completed, the mixture is heated to 180° C. until the reaction system becomes viscous. An excess of 2 mol / L hydrochloric acid is added to the reaction system, and the mixture is stirred until a flocculent precipitate is produced. The precipitate is filtered, washed three times with deionized water, and dried at 90° C. for 12 hours to obtain the synergistic flame retardant.

2. The fire-retardant polymer composite material according to claim 1, characterized in that: In the step (1), the feed mass ratio of binaphthol phosphate, 9,9'-(6-chloro-1,3,5-triazine-2,4-diyl)bis(9H-carbazole) and N,N-dimethylformamide is 20-45:10-30:120-200.

3. The fire-retardant polymer composite material according to claim 2, characterized in that: In the step (2), the feed mass ratio of the intermediate, the heterocyclic diamine monomer, N-methyl-2-pyrrolidone, anhydrous potassium carbonate and xylene is 12-42:18-38:80-150:5-12:30-50.

4. The fire-retardant polymer composite material according to claim 3, characterized in that: The heterocyclic diamine monomer is one of 2-(4-aminophenyl)-5-aminobenzimidazole, 2-(4-aminophenyl)-5-aminobenzoxazole and 2,5-di(4-aminophenyl)oxadiazole.

5. The fire-retardant polymer composite material according to claim 4, characterized in that: The weight average molecular weight of the polyimide is 20,000-40,000, and the weight average molecular weight of the polyurethane is 20,000-30,000.

6. The fire-retardant polymer composite material according to claim 5, characterized in that: The lubricant is a combination of one or more of sodium bentonite, calcium bentonite, graphite, zinc naphthenate, and molybdenum disulfide.

7. The fire-retardant polymer composite material according to claim 6, characterized in that: The antioxidant is a combination of one or more of ammonium polyphosphate, melamine, 2-mercaptobenzimidazole, N-phenyl-α-naphthylamine, and N-(1,3-dimethylbutyl)-N'-phenyl-1,4-phenylenediamine.

8. The fire-retardant polymer composite material according to claim 7, characterized in that: The antioxidant is a combination of one or more of tris(2,4-di-tert-butyl)phenyl phosphite, tris(2,4-di-tert-butylphenyl)phosphite, pentaerythritol tetrakis(3,5-di-tert-butyl-4-hydroxy)phenylpropionate, and bis-(2,4-di-tert-butylphenyl)-pentaerythritol diphosphite.

9. The fire-retardant polymer composite material according to claim 8, characterized in that: The preparation is carried out by the following steps: polyamide and polyurethane are mixed evenly, added into a twin-screw extruder, a synergistic flame retardant, a lubricant, an antioxidant and an anti-aging agent are added into the middle section of the twin-screw extruder, melt-extruded through the twin-screw extruder, and dried to obtain the polymer composite material.

10. The fire-retardant polymer composite material according to claim 9, characterized in that: The temperature of the twin-screw extruder is 220-270°C.